Problematika Pembelajaran Daring Bagi Guru Dan Siswa - Novianti, Dessi; Naldo, Jufri; Ali, M. Nasihudin (CV. ITTC INDONESIA, 2023)
This research explains the problems of online learning that occurred during the Covid-19 pandemic. This research aims to find out the effectiveness of online learning during the pandemic, find out the obstacles that occur and the solutions provided by schools for teachers and students who are stuttering with technology. This research uses cybernetic learning theory and digital divide theory. This research uses descriptive qualitative research methods. Primary data sources in this study are the results of interviews and observations with teachers, parents of students and students who take part in online learning. Each consisting of 3 resource persons and secondary data sources come from theoretical studies of journals and books. The results of this study show that the online learning system implemented by the government is less effective. This is due to the many obstacles that occur during the learning process, obstacles that occur such as problematic networks, internet quota packages that are few and quite expensive, the absence or limitation of smartphones to carry out online learning. However, as long as all parties involved work together, the obstacles that occur will be reduced and even resolved properly.